Information without power? Exploring the challenges and opportunities in the usage of the Promotion of Access to Information Act no 50 of 2000 (PAIA) as a potent tool for advancing socio-economic justice in South Africa Langton Miriyoga. - Miriyoga, Langton (Department of Public Law, 2014)
Includes abstract.